Dynamic of mitochondrial network, cristae, and mitochondrial nucleoids in pancreatic β-cells - Ježek, Petr; Dlasková, Andrea (Mitochondrion, 2019)
Type 2 diabetes progression stems from dysfunction of β-cells, besides the peripheral insulin resistance. Mitochondria as glucose sensor and regulation center are impaired at various stages of this progression. Their biogenesis and functional impairment is reflected by altered morphology of the mitochondrial network and ultramorphology of cristae and mitochondrial DNA loci, termed nucleoids. Aspects of all above changes are reviewed here together with a brief introduction to proteins involved in mitochondrial network dynamics, cristae shaping, and mtDNA nucleoid structure and maintenance. Most frequently, pathology is reflected by the fragmentation of network, cristae inflation or absence and declining number of nucleoids.
Keywords: Animals; Diabetes Mellitus, Type 2; Mitochondrial Membranes; mitochondrie; Insulin-Secreting Cells; beta-buňky; lidé; mitochondriální dynamika; zvířata; Mitochondrial Dynamics; Mitochondria; diabetes mellitus 2. typu; mitochondriální membrány; Humans